Oral Hygiene as a Risk Factor in Periodontitis - Abdul Majeed Wadi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Dental plaque is the etiological factor for initiation of periodontal disease due to secretion of toxins andproteolytic enzymes by the microbial accumulation in the cervical region of teeth & sub gingival area.Gingival inflammation will progress into the continuing destruction of supporting tissues like resorptionof alveolar bone Joss of attachment increase pocket depth if we don’t remove the microbial dental plaque,by daily oral hygiene practice through mechanical tooth brushing of the person himself &periodic clinicalexamination to remove the plaque .calculus &other retentive factors to maintain the oral hygiene in a goodmanner.The oral hygiene is considered as a risk factor in the prevention or progression of periodontal diseasedepending on daily removing of dental plaque by the person & professional recalling system clinically.